2010
DOI: 10.1096/fj.09-144923
|View full text |Cite
|
Sign up to set email alerts
|

Glut2‐dependent glucose‐sensing controls thermoregulation by enhancing the leptin sensitivity of NPY and POMC neurons

Abstract: The physiological contribution of glucose in thermoregulation is not completely established nor whether this control may involve a regulation of the melanocortin pathway. Here, we assessed thermoregulation and leptin sensitivity of hypothalamic arcuate neurons in mice with inactivation of glucose transporter type 2 (Glut2)-dependent glucose sensing. Mice with inactivation of Glut2-dependent glucose sensors are cold intolerant and show increased susceptibility to food deprivation-induced torpor and abnormal hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 54 publications
(60 reference statements)
4
79
0
1
Order By: Relevance
“…Our studies on NTS Glut2-expressing neurons have shown that these are indeed activated by hypoglycaemia to control parasympathetic activity and glucagon secretion [75]. On the other hand, Glut2-expressing neurons of the basolateral medulla are activated by glucose injections as revealed by c-fos immunostaining [63]. Whether they are GE neurons that negatively control glucagon secretion will, however, require direct analysis using electrophysiological and optogenetic techniques.…”
Section: Summary and Perspectivesmentioning
confidence: 91%
See 2 more Smart Citations
“…Our studies on NTS Glut2-expressing neurons have shown that these are indeed activated by hypoglycaemia to control parasympathetic activity and glucagon secretion [75]. On the other hand, Glut2-expressing neurons of the basolateral medulla are activated by glucose injections as revealed by c-fos immunostaining [63]. Whether they are GE neurons that negatively control glucagon secretion will, however, require direct analysis using electrophysiological and optogenetic techniques.…”
Section: Summary and Perspectivesmentioning
confidence: 91%
“…This was shown by the much lower hypothermic response induced by i.c.v. 2-DG injections in RIPGlut1;Glut2 −/− as compared with control mice [63]. This was secondary to reduced activation of brown fat uncoupling protein 1 and deiodinase-2 expression by the sympathetic nervous system and was associated with fastinginduced torpor in the Glut2-null mice.…”
Section: Glucose Sensing Feeding and Thermogenesismentioning
confidence: 92%
See 1 more Smart Citation
“…However, those that exist have been corroborated by the use of mice expressing a fluorescent reporter gene (eYFP) under the control of the GLUT2 promoter, GLUT2‐eYFP mice (Mounien et al, 2010). GLUT2 was found in neurons and astrocytes dispersed in many structures, including the hypothalamus, the brain stem, the thalamic area (Arluison, Quignon, Thorens, Leloup, & Penicaud, 2004; Labouebe, Boutrel, Tarussio, & Thorens, 2016) and in tanycytes (Garcia et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, GLUT2‐positive α2‐ and β1‐tanycytes are located in the lateral walls of the 3V and make contact with orexigenic AN neurons, which produce neuropeptide Y (NPY) and agouti‐related protein (AGRP), and anorexigenic AN neurons, which produce proopiomelanocortin (POMC) and the cocaine‐amphetamine‐regulated transcript (CART), through their extensive processes (Broberger, Johansen, Johansson, Schalling, & Hokfelt, 1998; Elias et al, 1998; Kristensen et al, 1998). Interestingly, GLUT2‐eYFP mice showed the absence of labeling in POMC or NPY neurons (Mounien et al, 2010); however, these mice showed labeled nerve terminals, presumably from GLUT2‐expressing cells, which have their soma outside the AN, suggesting an indirect control of AN neurons by glucose (Mounien et al, 2010; Thorens, 2005). Recently, GLUT2 was also detected in neurons of the nucleus tractus solitarius (NTS), specifically in a hypoglycemia‐activated neuronal population, which stimulates vagal activity and glucagon secretion, indicating a role for GLUT2 in the hypoglycemic condition (Lamy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%